Poetics of Transcendence: Stylistic Reduction as a Tool for Representation of Sacred Meanings - Brazgovskaya, Elena (Respectus Philologicus, 2016)
The main direction of the work is connected to the representation of abstract (transcendent) objects in music and literature. The article analyses “Cantus in Memoriam Benjamin Britten” by Arvo Pärt and some poems of Czesław Miłosz. The metaphysical dimension of reality involves forms and things, existing beyond the boundaries of empirical perception and, at first sight, beyond the descriptive practices. Abstract objects are available in intellectual experience, but culture must transform them into a symbolic form. As a rule, it is connected to the practice of art minimalism. The essence of minimalism is the reduction of number of stylistic tools and “purification” the perception from the visual / auditory images (not a mimetic use of language). For the representation of the sacred Pärt uses only mensural canon form, scale and chord. These “characters” are deprived of descriptive function, but have symbolic potential (canon as a sign of stopped time, the eternal return). The distinctive feature of the Miłoszʼs style is the pursuit to “clean” the signs (indexical and symbolic). There is the reverse side of language distillation: the rejection of the subjective position, emotional experience, the distance between the person and the object of representation.